Atypical retiform hemangioendothelioma arising in a patient with Milroy disease: a case report and review of the literature. (16th November 2016) - Arriola, Aileen Grace P.; Taylor, Laura A.; Asemota, Eseosa; Boos, Markus D.; Elder, David E.; Weber, Kristy L.; Micheletti, Robert G.; Zhang, Paul J.
Abstract : Retiform hemangioendothelioma (RH) is a rare vascular neoplasm with a high rate of local recurrence and low metastatic potential. We describe an unusual case of RH in a 45‐year‐old patient with Milroy disease, with a prominent solid component diffusely involving a chronic lymphedematous leg. This case is consistent with the postulated relationship between lymphedema and vascular neoplasms developing as a result of local immune dysfunction, and highlights the need to closely monitor patients with Milroy disease for pathologic changes. Our case highlights a unique example of RH with atypical features. There are several noteworthy unusual clinical and histologic findings including diffuse involvement of an entire limb, solid component with cytologic atypia, D2‐40 expression, and first‐time‐reported association with Milroy disease. Given the atypical histologic presentation of cytologic atypia, solid areas and atypical immunohistochemical profile with D2‐40 positivity, this case could cause diagnostic difficulty, especially in the setting of such a broad clinical differential.